Impact of emotional intelligence on employees turnover rate in FMCG organizations - Razi Sultan Siddiqui; Atif Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The study has been designed to determine the impact of emotional intelligence (EI) on turnover rate of first line managers of FMCG organizations in Karachi. It is generally believed that low emotional intelligence is a determinant of high turnover rate in first line managers of the FMCG organization. A sample of 40 employees from different FMCG organizations of Karachi who are performing their duties at first line management level falling within the age range of 20-40 years, with education level from Intermediate to Masters has been drawn randomly. Personal information of the participants is collected through demographic information sheet. TEIQue (Petrides & Furnhm, 2003) questionnaire is used to measure the variables of employees' turnover and trait emotional intelligence. All participants have to respond on a seven point Likert scale. A higher score on this scale indicates higher level of emotional intelligence. In order to analyze the data, Statistical Package for Social Science (SPSS, V, 12) is applied. Descriptive statistics (mean and standard deviation) is applied to study the sample characteristics and linear regression analysis and Karl Pearson's Coefficient of Correlation (Pearson's product moment correlation coefficient) is calculated. This analysis shows strong impact of low emotional intelligence with increased employee job turnover rate.
Keywords: 330; job satisfaction; employee's turnover rate; emotional intelligence